Sustainable Development Goals and Addressing Noncommunicable Diseases - Rath, Seema; Patnala, Shraddha; Bosman, Sean James; Srinivas, Sunitha (Indian Journal of Pharmacy Practice)
Sustainable development can be achieved by eradicating poverty, attaining the wellbeing of the population, and by protecting and improving environments by restricting pollution. Non communicable Diseases (NCDs) are currently responsible for 68% of global deaths and are projected to result in 75% of global deaths by 2030. They account for a large proportion of premature deaths (42%), and most of these casualties occur in developing countries (80%). Thus the increasing burden of NCDs is bound to affect both the levels of poverty and the sustainable development of developing countries much more than it will impact on developed countries. Sustainable Development Goal (SDG) 3.4 has thus been formulated to emphasise the reduction of premature mortality from NCDs by one third, through prevention and treatment thereof, and by promoting mental health and well-being for all by 2030. NCDs are also indirectly related to SDG 3.5, which aims to strengthen the prevention and treatment of substance abuse; SDG 3.8 aims at universal health coverage (UHC); and SDG 3.9 targets asubstantial reduction in the number of deaths and illnesses from pollution and contamination by 2030. To achieve these targets it is necessary to have major interventions to deal with rapid unplanned urbanization and the globalization of markets that promote inactivity and unhealthy diets, as well as to prevent and control pollution, and to plan and implement efficient UHC policies. With the shortage of resources at their disposal, it will be required for developing countries to prevent and control NCDs by focussing more on modifiable risk factors, with all of the stakeholders-the governments, educational institutions, private sector, non-governmental organisations and the community-playing proactive roles.
Keywords: Sustainable development; Non-communicable diseases; Low and middle income countries; India